Preparation of adsorbents for the extraction of heavy metals from mining wastewater - Elena I. Mirzaeva; Nurkhon F. Isaeva; Elmurod Ya. Yalgashev; Dilnoza P. Turdiyeva; Rufatjon M. Boymonov (Горные науки и технологии)
Mining and metallurgical operations are inextricably connected with the consumption of large volumes of water and, consequently, the generation of liquid waste. The priority is to solve the problems of treatment and rational reclaiming of process waters with high content of valuable components. This will make it possible to obtain a significant environmental and economic effect, i.e. to bring profit directly to enterprises, save material resources and reduce the environmental impact in mining regions. Processing of copper-zinc ores is accompanied by the formation of metal-bearing wastewater with a wide range of associated metals and nonmetals with low concentrations of each individual component and pH fluctuations within wide ranges. These factors make it difficult to select a rational treatment technology, so enterprises have to pay for excessive metal-bearing discharges into the environment. Heavy metals are toxic, do not undergo decomposition, can be accumulated by aquatic plants and reach a human body through the food chain. Centralized accumulation of accidental discharges, surface and drainage water with subsequent treatment for use in recycled water supply can solve a number of environmental problems in the field of water resources protection. Adsorption of heavy metals by zeolites produced from inexpensive clay minerals due to the simplicity of the process, possibility of zeolite regeneration, high efficiency in Cu2+, Zn2+ and Fe2+ ion exchange with release of non-toxic Na+ cations into the environment is a good alternative to chemical precipitation. The purpose of this study is to optimize the conditions for producing zeolites from kaolin and bentonite with the assessment of the possibility of their use for the treatment of wastewater generated during mining and processing of ores from sulfide copper-polymetallic deposits. The technology of alkaline fusion of bentonite or kaolin with sodium hydroxide was used as a basis for zeolite synthesis from crude mining products. The novelty of the technological approach in obtaining zeolites from natural aluminosilicates in comparison with the published data is that the adjustment of the chemical composition of alkaline alloy for the synthesis of zeolites with a certain crystal structure was carried out using Al2O3–NaAlО2 waste suspension. The alkaline alloy was dissolved in water, filtered, and subjected to hydrothermal crystallization. The phase composition of the zeolite adsorbents was studied. Through studying the recovery of heavy metals from model solutions, the mass composition and conditions of alkaline fusion processes as well as the hydrothermal crystallization mode were optimized. The achieved metal recovery of 95% from the model solutions with initial concentration (mg/L): 150 Cu2+, 180 Zn2+ and 125 Fe2+ allowed to draw the conclusion that zeolites based on bentonite and kaolin can be used in the treatment of metal-bearing wastewater.